Can probiotic, prebiotic, and synbiotic supplementation modulate the gut-liver axis in type 2 diabetes? A narrative and systematic review of clinical trials - Al-Najjar, Yousef; Arabi, Maryam; Paul, Pradipta; Chaari, Ali (Frontiers in Nutrition, 2022)
Background: Type 2 diabetes, one of the most common noncommunicable diseases, is a metabolic disorder that results in failed homeostatic control in several body systems, including hepatic function. Due to the gut microbiome’s potential role in diabetes’ pathogenesis, prebiotics, probiotics, and synbiotics have been proposed as complimentary therapeutic approaches aimed at microbiota readjustment. Methods: A systematic review was conducted on PubMed, Scopus, Web of Science, Embase, and Cochrane examining the effect of probiotics, prebiotics, and synbiotics on hepatic biomarkers in patients with diabetes. Results: From 9,502 search hits, 10 studies met the inclusion criteria and were included in this review. A total of 816 participants (460 intervention and 356 control) were investigated for the effects of nine different hepatic biomarker measurements including aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total protein, bilirubin, liver steatosis, liver stiffness, fatty liver index, and gamma-glutamyl transferase levels. Of the 13 interventions groups analyzed from the 10 studies, 3 were prebiotic interventions, 3 were single strain probiotic interventions, 3 were multi-strain probiotic interventions, and 4 were synbiotic interventions. Nutraceuticals used in these trials included six genera of bacteria (Lactobacilli, Bifidobacteria, Streptococci, Acetobacters, Lactococci, and Propionibacteria), five different prebiotic formulations (inulin, inulin & beta carotene, chicory inulin enriched with oligofructose, galacto-oligosaccharides syrup, and powdered cinnamon), or a combination of these to form multi-strain probiotics or synbiotics. Conclusion: Although some studies showed insignificant changes in hepatic biomarkers, generally the results yielded a decrease in liver damage by the reduction of oxidative stress, pro-inflammatory cytokines, gut dysbiosis, and insulin resistance which led to improvements in hepatic biomarker levels.